Seismic Behaviors and Resilience of Concrete-encased Concrete-Filled Steel Tubular Columns with Debonded High-Strength Rebars: Experiment and Assessment. Issue 15 (18th November 2022) - Wang, J.H.; Sun, Y.P.
ABSTRACT: A total of six cantilever square concrete-encased CFST columns were fabricated for testing under both lateral load and constant compressive load. The debonded high-strength PSB 930 steel rebars were used as the longitudinal rebar to provide resilience for specimen columns. Experimental results indicated that the specimens with debonded PSB longitudinal rebars had smaller residual deformation and smaller yield sectional stiffness compared with the specimen with normal steel rebars because the yielding progress of the longitudinal rebar was delayed. Based on the parametric analytical results, some models are proposed to assess the yield and post-yield sectional stiffness and the residual drift.